A wide circularly polarized dual‐band isosceles trapezoidal monopole antenna with modified ground plane. (8th November 2021) - Bag, Biplab; Biswas, Sushanta; Sarkar, Partha Pratim
Summary: In this paper, a simple wideband circularly polarized monopole antenna for different wireless and satellite communication applications is proposed. The top plate of the antenna is composed of an isosceles trapezoidal patch with an inverted L‐shaped strip connected along with this. The bottom side (ground plane) has been modified by embedding two right‐angle triangular stubs for enhancing the impedance and CP performances. The proposed antenna is designed and fabricated on commercially available FR4 substrate occupying the volume of 0.525λ₀ × 0.42λ₀ × 0.0168λ₀. The −10‐dB reflection coefficient bandwidth exhibits two wide bands of 1530 MHz (2.6 GHz to 4.13 GHz) and 2040 MHz (6.93 GHz to 8.97 GHz). The measured 3‐dB AR bandwidth is 1800 MHz (6.6 GHz to 8.4 GHz), covering International Tele‐communication Union for satellite communication bands (uplink and downlink). In addition, the proposed monopole antenna has also provided good gain ≥5dBi for both the bands. Abstract :